Heating performance of an air source heat pump with a portable thermoelectric subcooler - Yifeng Hu; Bo Shen; Sreenidhi Krishnamoorthy; Don Shirey (Case Studies in Thermal Engineering)
This study investigates the heating performance of an integrated air-source heat pump (ASHP) with a thermoelectric subcooler (TES) module, revealing significant performance enhancements, particularly in colder temperatures. Results show that adding the portable TES boosts the ASHP's heating capacity, making it feasible for residential applications. The coefficient of performance (COP) for the TE system, which is influenced by condensing temperatures and ambient conditions, ranges from 1.51 to 2.07. If condensing temperatures are consistently maintained above 35 °C, a TE COP of approximately 2.07 is achievable, supporting system downsizing and reducing supplemental heating. When coupled with an oversized indoor coil, the TES-ASHP system delivers comparable heating to a baseline unit while achieving a 10 % higher COP. Capacity increases by 8.7 %–24 % with TES in colder conditions, though COP declines by 9 %–18 %, diminishing as temperatures drop. Compared to systems with supplemental heating, this setup achieves a COP 10 %–17 % higher. Future work will involve extended field testing in various climates, exploration of advanced materials for thermal efficiency, and assessment of alternative refrigerants to improve performance and sustainability. This integrated ASHP-TES system holds promise for increased efficiency and reduced environmental impact in cold climates.